2021
DOI: 10.3390/v13081461
|View full text |Cite
|
Sign up to set email alerts
|

An Epitope Platform for Safe and Effective HTLV-1-Immunization: Potential Applications for mRNA and Peptide-Based Vaccines

Abstract: Human T-cell lymphotropic virus type 1 (HTLV-1) infection affects millions of individuals worldwide and can lead to severe leukemia, myelopathy/tropical spastic paraparesis, and numerous other disorders. Pursuing a safe and effective immunotherapeutic approach, we compared the viral polyprotein and the human proteome with a sliding window approach in order to identify oligopeptide sequences unique to the virus. The immunological relevance of the viral unique oligopeptides was assessed by searching them in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Our vaccine design centered on the envelope glycoprotein gp62, a key outer membrane protein containing numerous epitope binding sites crucial for the infectious process and immune response of HTLV [70,71]. Epitope mapping was executed to identify T cell and B cell epitopes, both essential for provoking the host's immune response to viral infection [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…Our vaccine design centered on the envelope glycoprotein gp62, a key outer membrane protein containing numerous epitope binding sites crucial for the infectious process and immune response of HTLV [70,71]. Epitope mapping was executed to identify T cell and B cell epitopes, both essential for provoking the host's immune response to viral infection [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine was designed by targeting the envelope glycoprotein gp62, an outer membrane protein having a greater number of epitope binding site that plays a significant role in the infectious process and immune response of HTLV (67,68). The selected proteins were predicted to be antigenic and having desirable biophysical properties that are expected in vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the knowledge advances in the HTLV-host interaction and in the biotechnology recent systematic reviews and reports showed a plethora of approaches for HTLV-1 vaccine candidates: viral like particles vectors and viral vectors (Vaccinia virus, Adenovirus and Sendai virus), dendritic cell and peptide-based vaccines, recombinant single proteins or multiepitope proteins expressed in different systems including molecules encapsulated using nanotechnology [ 9 13 ]. Of great interest 15 peptide stretches (from Gag and Gag-Pro-Pol polyproteins, Tax-1 and gp62) were presented from an epitope platform for HTLV-1 vaccine development of uniquely viral non-human pentapeptides to avoid cross-reaction, generating safe immunization based on peptides and mRNA [ 14 ].…”
Section: Introductionmentioning
confidence: 99%